(untitled) (Biological Sciences - PJSIR, 1994)
rial obtained from ’cells A’ but at no higher dilutions, whereas a titre of 1000 HU/ml was found in material obtained from ’cells B’ which was suspended in induction buffer without added chloramphenicol (Table 1).